2022
DOI: 10.1002/pssa.202200073
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of the Thermoelectric Properties of Fe‐Substituted Icosahedral Al–Pd–Re Quasicrystals

Abstract: Icosahedral quasicrystals (QCs) have a glass‐like, low thermal conductivity because of their complex crystal structures, and a moderate power factor because of deep pseudogap formation in their electronic density of states (DOS) at the Fermi level originating from icosahedral symmetry and covalent bonding nature. These features are beneficial for high‐performance thermoelectric materials. Densified bulk samples of icosahedral Al–Pd–Re–Fe QCs are synthesized by arc‐melting, annealing, and spark plasma sintering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…We confirmed that all synthesized bulk samples were identified as an F -type quasi-crystalline phase [ 26 ], as shown in Figure 1 A. In the Al–Pd–Re–Co system, the formation of 2/1- or 1/1-approximant crystal was not realized, unlike in Al–Pd–Re–Ru [ 27 ] and Al–Pd–Re–Fe [ 16 ] quaternary systems. We observed peak shifting to a higher degree with increasing x , indicating that the quasi-lattice constant ( a R ) decreased by Co substitution for Re ( Figure 1 B).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…We confirmed that all synthesized bulk samples were identified as an F -type quasi-crystalline phase [ 26 ], as shown in Figure 1 A. In the Al–Pd–Re–Co system, the formation of 2/1- or 1/1-approximant crystal was not realized, unlike in Al–Pd–Re–Ru [ 27 ] and Al–Pd–Re–Fe [ 16 ] quaternary systems. We observed peak shifting to a higher degree with increasing x , indicating that the quasi-lattice constant ( a R ) decreased by Co substitution for Re ( Figure 1 B).…”
Section: Resultssupporting
confidence: 76%
“…The relative density of the sample with x = 0 was 95.7% [ 16 ], indicating that a dense bulk sample was fabricated by the SPS process. The ideal densities of the Co-substituted samples were calculated from d bulk (relative density: ~100%, 6.30 g cm –3 ) of the sample with x = 0 [ 22 ] and the rate of change in average atomic weight ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations